Optical Coherence Tomography Angiography to detect non-exudative neovascular age-related macular degeneration mimicking chronic central serous chorioretinopathy. - Manuel A P Vilela (Indonesian Vitreoretinal Society, 2020)
Chronic central serous chorioretinopathy (cCSC) can produce an overlap of signs that can be difficult to distinguish from cases with non-exudative neovascular age-related macular degeneration (nneAMD). Around 2-10% of the patients with cCSC will develop neovascularization. Sometimes both diseases could be present at the same individual. The purpose of this narrative review is to discuss the current information concerning the signs in OCT angiography that eventually could help to differentiate these situations and analyze the best diagnostic evidence.